2008
DOI: 10.1111/j.1460-9568.2008.06482.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Ser704Cys DISC1 polymorphism with human hippocampal formation gray matter and function during memory encoding

Abstract: A common nonsynonymous single nucleotide polymorphism leading to a serine-to-cysteine substitution at amino acid 704 (Ser 704 Cys) in the DISC1 protein sequence has been recently associated with schizophrenia and with specific hippocampal abnormalities. Here, we used multimodal neuroimaging to investigate in a large sample of healthy subjects the putative association of the Ser 704 Cys DISC1 polymorphism with in vivo brain phenotypes including hippocampal formation (HF) gray matter volume and function (as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 46 publications
2
63
1
1
Order By: Relevance
“…In agreement with a previous report (Di Giorgio et al, 2008), we demonstrated that healthy Cys-carriers had smaller parahippocampal gyrus (PHG) and hippocampal volume than healthy Ser-homozygotes. The PHG has an important role in episodic memory (de Curtis and Pare.…”
Section: Effect Of Ser704cys On the Healthy Brainsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with a previous report (Di Giorgio et al, 2008), we demonstrated that healthy Cys-carriers had smaller parahippocampal gyrus (PHG) and hippocampal volume than healthy Ser-homozygotes. The PHG has an important role in episodic memory (de Curtis and Pare.…”
Section: Effect Of Ser704cys On the Healthy Brainsupporting
confidence: 93%
“…Groups did not differ in genotype distribution (c 2 (6) ¼ 3.36, p ¼ 0.76). We compared Cys-carriers (Cys/Cys-and Cys/Ser-genotypes) with Ser-homozygotes, based on the small amount of Cys-homozygotes and in agreement with the literature (Hashimoto et al, 2006;Callicott et al, 2005;Di Giorgio et al, 2008;Prata et al, 2008;Brauns et al, 2011;Takahashi et al, 2009). …”
Section: Genotypingmentioning
confidence: 94%
See 1 more Smart Citation
“…Another group investigated the same SNP, but their findings were not convergent with those of the Callicott group (Di Giorgio et al 2008). Eighty healthy controls were scanned during encoding and retrieval of novel, complex scenes of neutral emotional valence.…”
Section: Genetic Approachmentioning
confidence: 97%
“…One of the natural schizophrenia risk DISC1 polymorphisms, S704C (10,11), shown to affect the function of prefrontal cortex, is also localized in its C-terminal domain (12,13). This SNP has been observed to function at the molecular level, as DISC1-S704C affects the localization of key PCM1 (pericentriolar material protein-1) to the centrosome (14).…”
Section: Disc1mentioning
confidence: 99%